Horacio Quiroga e Buenos Aires: o diálogo com a metrópole pelas páginas das novelas de folhetim - Leites, Amalia Cardona (2015)
The insertion of an established writer as the Uruguayan short story writer Horacio Quiroga in the gender of serial novels, through six narratives published in illustrated magazines such as Caras y Caretas and Fray Mocho between the years 1908 and 1913 shows the writer s inclination to adapt, through the work with a genre which he previously had no affinity with, to a modern scenery in which the very concept of literary work began to undergo questioning and transformation. But the complexity of these six short novels goes far beyond their aesthetic and their particular narrative matrix, raising questions concerning the social and ideological problems encountered in the first decades of a Buenos Aires in transformation. Products of the cultural industry, these novels cannot be understood as mere impoverished imitations of the canonical literature, but neither they represented the expression of a popular culture that resisted and opposed to the dominant culture. They are best seen as belonging to an area of dispute, to a field of cultural struggle. The recognition of these novels, their circulation and their consumption, is what does not allow us to deny the existence of a huge readership that did not match the expectations of the literate elite. Here is precisely where their value lies: they are witnesses of the Apocalypse that occurs when literature ceases to be a realm reserved for those higher spirits who understand it, and begins to suffer an irrevocable closeness to the public.